ANALISIS PENERIMAAN RETRIBUSI PARKIR SEBELUM DAN SESUDAH DITERAPKANNYA E-PARKING PADA DINAS PERHUBUNGAN KOTA MEDAN - Andini, Alyuna; Damanik, Destari; Eka Susilawaty, Tengku (JURNAL PERPAJAKAN, 2024)
Andini, Alyuna. 2023. "Analysis of Parking Levy Receipts Before and After the Implementation of E-Parking at the Medan City Transportation Office". D3 Taxation Study Program, Faculty of Social Science. Universitas Pembangunan Panca Budi Medan. Final Project. This study aims to determine the Receipt of Parking Retribution Before and After the implementation of E-Parking at the Medan City Transportation Office. The research method used in this study is descriptive analysis. With this method, research data is compiled, interpreted, explained, and analyzed. The type of data used in this study used qualitative data and data obtained from the Medan City Transportation Office.